Kinerja Keuangan Memediasi Dana Perimbangan, Alokasi Belanja Daerah Pada Indeks Pembangunan Manuasia dan Pertumbuhan Ekonomi - Aryawati, Ni Putu Ari; Sudana, I Putu (Jurnal Ilmiah Akuntansi dan Bisnis; Vol 13 No 1 (2018), 2018)
The aim of this study was to analyzes whether the fiscal balance transfer, regional allocation budget and regional financial performance directly affects the human development index and economic growth in the Regency / City throughout West Nusa Tenggara Province and indirect effect of fiscal balance transfer and regional allocation budget on human development index and economic growth with the financial performance as a mediating variable. Analysis of the data in this research used Partial Least Square (PLS) analysis. The results of the analysis show that there are positive affect between fiscal b alance transfer and regional a llocation budget on economic growth. R egional a llocation budget ha s negative affect to HDI. Regional allocation budget influen ce partial mediation on human development index and economic growth with regional financial performance as a mediating variable. The result of this study, to maximize the HDI and economic growth of West Nusa Tenggara Province s hould consider the amount of fiscal b alance transfer , regional a llocation budget and regional financial performance because the variables are proven to affect HDI and economic growth of West Nusa Tenggara Province either directly or indirectly. Keywords: HDI , Economic Growth, Regional Financial Performance